Dentistry and Dental Hygiene Handbook - New York State Education Dept., Albany. Office of the Professions; New York State Education Dept., Albany. Office of the Professions ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
A reference guide to laws, rules, and regulations that govern dentistry and dental hygiene practice in New York State is presented. In addition to identifying licensing requirements/procedures for dentists and dental hygienists, general provisions of Title VIII of the Education Law are covered, along with state management, professional misconduct, and unauthorized acts. Regulations of the Commissioner of Education are also provided, along with an application form for license and first registration, a certification form of professional education, a certification form of licensure, and a personal affidavit of professional practice. Rules of the New York Board of Regents on unprofessional conduct are also presented, including general provisions for all professions, general provisions for health professions, and special provisions for the dental and dental hygiene professions. Also provided is a U.S. and Canadian state/province listing of accredited dental programs, with the college's address, and the name of the dean of the dental school. Accredited dental hygiene programs in the United States and Canada are listed. (SW)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Allied Health Occupations Education; Certification; College Programs; Credentials; Dental Hygienists; Dentistry; Higher Education; Medical Education; Records (Forms); State Agencies; State Boards of Education; State Legislation; State Licensing Boards; State Standards; New York; Guides, Non-Classroom.; Legal/Legislative/Regulatory Materials; Tests/Questionnaires.